Social protection and employment in Africa's agricultural sector - Romanus Osabohien; Olaronke Toyin Onanuga; Busayo Aderounmu; Oluwatoyin A. Matthew; Evans Osabuohien (Verslas: Teorija ir praktika / Business: Theory and Practice, 2020)
Social protection is increasingly becoming a powerful tool for enhancing productivity and employment and is, therefore, important for Africa's agricultural transformation. Thus, this study aims at examining how Africa's agricultural sector can be transformed through social protection policies and programmes for employment. It applies the Feasible Generalised Least Squares (FGLS) econometric method on a panel of 38 African countries with the data sourced from the Country Policy and Institutional Assessment (CPIA) and World Development Indicators (WDI) for the period 2005-2017. The results from the study show that social protection has a positive impact on employment outcomes through various channels such as building human resource, equity in the use of public resources, social inclusion, among others. The study concludes by recommending that the governments of African countries should implement effective social protection programmes and policies in the agricultural sector in form of insurance, in-kind and cash support, among others to make farming attractive, thereby increasing employment and productivity.
Keywords: O47; E61; Q12; 650; agricultural transformation; farming; productivity